Doctoral education in public affairs and administration: issues for the 1990s - Overman E. Sam; Radin Beryl A.; Perry James L.
This paper reprots the results of a 1990 survey of 60 NASPAA dectoral programs in descriptive date about a variety of facets of public affairs and administration doctoral programs: program and institutional structure, size, student diversity, number of degree granted, and faculty hires. Respondents identified five broad areas as sources for special concern for the design and operation of doctoral programs: (1) problems that stem from limited resource availability; (2) issues related to the quality of the educational program; (3) questions dealing with the definition of the scope of offerings and requirements; (4) considerations for the needs of part-time students; and (5) issues of minority recruitment and rete
Keywords: Public Affairs; National Association of Schools of Public Affairs and Administration (NASPAA); Doctoral Education; Public Administration -- Research -- U.S.A.